ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK DENGAN MODEL MAKE A MATCH DI KELAS IV SEKOLAH DASAR - Sakurdi Sakurdi; Siti Halidjah; Dyoty Auliya Vilda (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the thematic lesson plan with the make a match model in Class IV of 24 Southeast Pontianak Elementary Schools. The research method used is a descriptive method with a qualitative assessment form. The source of this assessment data is the fourth grade teacher of SD Negeri 24 Pontianak Tenggara. The data of this research are in the form of thematic learning implementation plan documents and the results of interviews with the fourth grade teachers of SD Negeri 24 Pontianak Tenggara. The results of the analysis show that the components of the learning implementation plan made by the teacher have not fully referred to the regulation of the minister of education number 22 of 2016 concerning process standards. Identity components, core competencies, learning objectives, learning materials and methods.Keywords: Learning Implementation, analysis, make a match model.